Português como língua de herança: estudo de caso sobre os desafios de aprendizagem na infância - Benedito, Neotides da Silva (2016)
This paper presents a study about the difficulties of a child to learn Portuguese as Heritage Language in the familiar environment. It presents literature data on the actors involved in the process of acquisition of PLH, with emphasis on family role. It highlights Kim's theory, based on the alternance of stress, adaptation and growth, which will define the internal dynamics of intercultural experiences in the process of learning a language, as a second one, as a heritage language. It tells the story of a 7 years old girl, daughter of Brazilian mother and German father, who initially refused to speak Portuguese. It presents the strategies adopted in order that this target could be achieved, and that included more active participation in social environments of learning, adoption of domestic practices of conversation, immersion in Brazilian culture through traveling to Brazil. It follows up the development of the child over a year, and at the end it compares the literature and the obtained results, proving the effectiveness of the adopted strategies.